PECULIARITIES OF THE BRANCHES OF LAW IN ANCIENT CHINA - Marilena-Oana NEDELEA (Eastern European Journal of Regional Studies)
The purpose of this paper is to examine the historical roots of the Chinese legal system who is one of the oldest in the world. China's legal system is largely a civil law system, although found its root in Great Qing Code and various historical system. The analyses of the Chinese law documents led to results that largely confirm that the Chinese have written their own laws since ancient times, a peculiarity which compares them, for the historical and characteristic period, with the Romans. Chinese law is a legal system integrated into a certain philosophical conception, namely Confucianism. The research methods used were: analysis, synthesis, deduction, analogy and comparison. The analysis of the Chinese legal system have allowed to reveal that different branches of law as civil law, family law, administrative law, and criminal law have some peculiarities in ancient Chinese laws that were presented in this article.